Antidepressants and mortality risk in a dementia cohort: data from SveDem, the Swedish Dementia Registry. (1st September 2016) - Enache, D.; Fereshtehnejad, S.‐M.; Kåreholt, I.; Cermakova, P.; Garcia‐Ptacek, S.; Johnell, K.; Religa, D.; Jelic, V.; Winblad, B.; Ballard, C.; Aarsland, D.; Fastbom, J.; et al.
Abstract : Background: The association between mortality risk and use of antidepressants in people with dementia is unknown. Objective: To describe the use of antidepressants in people with different dementia diagnoses and to explore mortality risk associated with use of antidepressants 3 years before a dementia diagnosis. Methods: Study population included 20 050 memory clinic patients from the Swedish Dementia Registry (SveDem) diagnosed with incident dementia. Data on antidepressants dispensed at the time of dementia diagnosis and during 3‐year period before dementia diagnosis were obtained from the Swedish Prescribed Drug Register. Cox regression models were used. Results: During a median follow‐up of 2 years from dementia diagnosis, 25.8% of dementia patients died. A quarter (25.0%) of patients were on antidepressants at the time of dementia diagnosis, while 21.6% used antidepressants at some point during a 3‐year period before a dementia diagnosis. Use of antidepressant treatment for 3 consecutive years before a dementia diagnosis was associated with a lower mortality risk for all dementia disorders and in Alzheimer's disease. Conclusion: Antidepressant treatment is common among patients with dementia. Use of antidepressants during prodromal stages may reduce mortality in dementia and specifically in Alzheimer's disease.